2006
DOI: 10.1590/s0103-73312006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Apresentação

Abstract: Em um de seus contos, João Guimarães Rosa 1 narra a história de Flausina, uma sertaneja em luta contra seu destino. Trata-se de uma mulher que, para poder encontrar a felicidade e o amor verdadeiro, elimina através de uma longa, penosa e bem executada estratégia, quatro homens de uma poderosa família, que a obrigaram de formas mais ou menos brutais a "casar-se" com eles. Morte física no caso deles e simbólica no caso dos filhos que ela lhes "deu" ao longo de grande parte de sua vida e que, agora, mantém distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…1 There are many different forms of violence in society but women are particularly vulnerable to gender and sexual violence. 2 The effect of violence against women involves society as a whole, since it occurs in almost all environments, even within socially privileged spaces such as universities. Studies conducted in universities in the United States, 3 Venezuela 4 and Chile 5 found that a large proportion of students had experienced some form of violence: 44.7% any form of violence in the USA study; 79% psychological violence in the Venezuelan universities and 17% of the female students in the Chilean university experienced unwelcome sexual advances.…”
Section: Introductionmentioning
confidence: 99%
“…1 There are many different forms of violence in society but women are particularly vulnerable to gender and sexual violence. 2 The effect of violence against women involves society as a whole, since it occurs in almost all environments, even within socially privileged spaces such as universities. Studies conducted in universities in the United States, 3 Venezuela 4 and Chile 5 found that a large proportion of students had experienced some form of violence: 44.7% any form of violence in the USA study; 79% psychological violence in the Venezuelan universities and 17% of the female students in the Chilean university experienced unwelcome sexual advances.…”
Section: Introductionmentioning
confidence: 99%